CPW balun for printed balanced antennas. Issue 11 (1st May 2014) - Sánchez, A.M.; Ribó, M.; Pradell, L.; Anguera, J.; Andújar, A.
Abstract : In coplanar waveguide (CPW) circuits, printed balanced antennas must be excited through baluns. These baluns often feature coplanar‐to‐slotline transitions that must be tuned and matched by electromagnetic optimisation, and may interfere with the antenna backward radiation. A new CPW balun for printed balanced antennas is presented and modelled. As its multimodal circuit model makes clear, it integrates an impedance‐matching network within its structure that can be analytically designed. The balun has been experimentally tested, exhibiting good agreement with its circuit model and a weak electromagnetic interaction with the antenna radiation.